Work Life Balance (WLB) dengan Kepuasan Kerja pada Guru - Adzani Inez Arisandy; Diah Sofiah; Hikmah Husniyah Farhanindya (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Teachers play various professional roles that can influence their work-life balance, which in turn affects job satisfaction. This study aims to examine the relationship between work-life balance and job satisfaction among teachers. A quantitative correlational approach was used. The subjects consisted of 47 teachers from SMPN 1 Ngronggot, Nganjuk, selected using the total sampling technique. The instruments used were the Work-Life Balance Scale by Fisher et al. (2009) and the Job Satisfaction Scale by Lester (1987). Data were analyzed using Pearson product-moment correlation. The results showed a significant positive relationship between work-life balance and job satisfaction (r = 0.407; p = 0.005). The higher the work-life balance, the higher the teachers’ job satisfaction. These findings highlight the importance of work-life balance in supporting teacher well-being and work performance. Keywords: job satisfaction; life balance; organizational psychology; teacher; work life balance Abstrak Guru menjalankan berbagai peran profesional yang dapat memengaruhi work life balance, akhirnya berpengaruh pada kepuasan kerja. Penelitian ini bertujuan untuk mengetahui hubungan antara work life balance dengan kepuasan kerja pada guru. Menggunakan pendekatan kuantitatif korelasional. Sebanyak 47 guru SMP Negeri 1 Ngronggot, Nganjuk yang dipilih menggunakan teknik total sampling. Instrumen yang dipakai adalah skala work life balance dari Fisher et al. (2009) dan skala kepuasan kerja dari Lester (1987). Analisis data dengan korelasi pearson product moment. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara work life balance dan kepuasan kerja (r = 0,407; p = 0,005). Semakin tinggi work life balance, semakin tinggi pula kepuasan kerja guru. Temuan ini menunjukkan pentingnya work life balance dalam mendukung kesejahteraan dan performa kerja guru. Kata kunci: guru; keseimbangan hidup; kepuasan kerja; psikologi organisasi; work life balance